2016
DOI: 10.1186/s12884-016-1109-3
|View full text |Cite
|
Sign up to set email alerts
|

Induced abortion - impact on a subsequent pregnancy in first-time mothers: a registry-based study

Abstract: BackgroundTo date, several studies concerning the effects of induced abortion (IA) on women’s later psychosocial well-being and future delivery complications have been published. However, the lack of reports on woman’s physical well-being during their first full-term pregnancy occurring after IA is what inspired the current study. Here, we evaluate the physical well-being and use of maternity services of first-time mothers with a history of IA.MethodsFinnish National Birth Registry data from 2008 to 2010 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
(14 reference statements)
0
4
0
1
Order By: Relevance
“…Interestingly, while one prior miscarriage was not found to be associated with preeclampsia, two or more miscarriages were found to be associated with increased risks of preeclampsia [ 7 ]. On the other hand, Holmlund et al found no association between induced abortion and preeclampsia in Finland [ 9 ]. Moreover, Clark et al reported no association between miscarriage and gestational hypertension, even in women with more than two abortions [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, while one prior miscarriage was not found to be associated with preeclampsia, two or more miscarriages were found to be associated with increased risks of preeclampsia [ 7 ]. On the other hand, Holmlund et al found no association between induced abortion and preeclampsia in Finland [ 9 ]. Moreover, Clark et al reported no association between miscarriage and gestational hypertension, even in women with more than two abortions [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of these studies are inconsistent; while some studies have reported an increased risk of preeclampsia in women with a history of abortions [ 5 – 8 ], others have reported no such effect [ 9 12 ] or a reduced risk of preeclampsia in women with a history of abortions [ 13 16 ]. Moreover, most these studies have been conducted in high-income countries [ 7 , 9 , 13 , 16 ]. There is a scarcity of data on the history of abortion and preeclampsia in sub-Saharan African countries [ 6 ], and none of these studies have been conducted in Sudan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inconsistency that emerged among the studies can at least partially be explained by differences in study design or power, by multiple comparisons, by recall bias and by differences in the methods used to perform IA at different times and in different countries. Additionally, epidemiological studies have been showed that revision of the uterine cavity might be responsible for endometritis, which is more likely to be the result of traumatic procedures 25 , 38 . This could also contribute to the differences in several studies.…”
Section: Discussionmentioning
confidence: 99%
“…Das Risiko für häufigere Fehlgeburten oder eine Plazenta praevia ist nicht erhöht[10].Das finnische Geburtsregister analysierte die Daten zwischen 2008 und 2010 von 57.406 Frauen kombiniert mit dem SAB-Register von 1983-2007 mit 5.167 Frauen. Es gab keine statistisch relevanten Unterschiede bezüglich der folgenden Schwangerschaft, Blutungen, schwangerschaftsinduziertem Hypertonus, Frühgeburtlichkeit, Anämie und vorgeburtlicher Kortisongabe[11].17.4 Mythos 4: Nach einer Abtreibung gibt es Probleme wieder ……”
unclassified